Properties of Hardened Concrete Produced by Waste Marble Powder - ARTIR, RECEP (ELSEVIER SCIENCE BV, 2015)
Marble is industrially processed by being cut, polished, and used for decorative purposes, and thus, economically valuable. In marble quarries, stones are cut as blocks through different methods. During the cutting process, 20-30% of a marble block becomes waste marble powder. Marble powder is a waste material generated in considerable amounts in the world. Marble waste leads to a serious environmental problem as well. Therefore, the use of waste marble in the concrete production as an admixture material or aggregate has increasingly become an important issue. In the present study, effect of different usage areas of waste marble on the hardened concrete properties was investigated based on previous studies. In this context, (1) compressive, flexural, and splitting tensile strength, (2) modulus of elasticity, (3) ultrasonic pulse velocity, (4) Schmidt surface hardness, and lastly (5) sorptivity coefficient/porosity of the hardened concrete, were examined. Comparing all results, the proposition the marble waste can be used in the production of concrete was discussed in a detailed manner. As a result, the use of waste marble powder in (1) conventional concrete mix, (2) self-compacting concrete mix, and (3) polymer concrete mix, was revealed. Consequently, it was found out that the use of waste marble in the conventional concrete mix as an admixture material or aggregate is suitable as it can improve some properties of the hardened concrete. However, the use of waste marble in the self-compacting and polymer concrete mixes as an admixture material or aggregate is not affected positively in terms of hardened properties of concrete. (C) 2015 Published by Elsevier Ltd.
Keywords: Concrete; Hardened Concrete; Recycling; Waste Marble Powder; MECHANICAL-PROPERTIES; DURABILITY; CEMENT; DUST